(untitled) (Journal of Academic Research, 2024)
This paper contains a direct proof of the result asserting that every Hausdorff topological vector space has a completion. The proof here is different from known proofs of this result, since it uses only the convergence of nets and their basic properties. The completion is constructed as equivalence classes of Cauchy sequences